2004
DOI: 10.1007/s10761-004-1137-y
|View full text |Cite
|
Sign up to set email alerts
|

Archaeological Explorations of Cultural Identity and Rural Economy in the North of Ireland: Goodland, County Antrim

Abstract: Renewed examination of an enigmatic settlement site perched atop a cliff above Murlough Bay in Goodland Townland, County Antrim, Northern Ireland calls into question long held ideas about Gaelic rural economy on the eve of the Ulster Plantation by reintroducing the complex cultural and political relationships between the north of Ireland and the Scottish isles. Long interpreted as temporary post-medieval booley huts associated with seasonal transhumance, recent reevaluation of the site suggests instead that Go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…The most well-known County Antrim site interpreted as a center for booleying activity lies to the north of Coolnagoppoge, and incorporates at least 129 huts in Goodland, Torglas, Knockbrack, and Bighouse townlands on the cliffs above Murlough Bay (Evans 1945;Graham 1954;Horning 2004b;O'Keeffe 2000;Williams and Robinson 1983). Excavations by Jean Graham in 1949 and 1950 and by Humphrey Case in 1952 and 1953 unearthed evidence for Neolithic use of the chalk land, but demonstrated that the huts were of post-medieval date (Case 1969(Case , 1973Case et al 1969;Graham 1954;Proudfoot 1958;Sidebotham 1950).…”
Section: Case Studies: Seasonal Landscapes Of County Antrimmentioning
confidence: 99%
See 2 more Smart Citations
“…The most well-known County Antrim site interpreted as a center for booleying activity lies to the north of Coolnagoppoge, and incorporates at least 129 huts in Goodland, Torglas, Knockbrack, and Bighouse townlands on the cliffs above Murlough Bay (Evans 1945;Graham 1954;Horning 2004b;O'Keeffe 2000;Williams and Robinson 1983). Excavations by Jean Graham in 1949 and 1950 and by Humphrey Case in 1952 and 1953 unearthed evidence for Neolithic use of the chalk land, but demonstrated that the huts were of post-medieval date (Case 1969(Case , 1973Case et al 1969;Graham 1954;Proudfoot 1958;Sidebotham 1950).…”
Section: Case Studies: Seasonal Landscapes Of County Antrimmentioning
confidence: 99%
“…Excavations by Jean Graham in 1949 and 1950 and by Humphrey Case in 1952 and 1953 unearthed evidence for Neolithic use of the chalk land, but demonstrated that the huts were of post-medieval date (Case 1969(Case , 1973Case et al 1969;Graham 1954;Proudfoot 1958;Sidebotham 1950). Extensive surveying was carried out in 2003, identifying three settlement clusters (Horning and Brannon 2004;Horning 2004b). The houses exhibit a similar degree of deterioration, several are associated with cultivation ridges, and one of the clusters includes compound huts wholly unlike the prototypical single-unit booley houses discussed by geographers (e.g., Evans 1945;Graham 1954;Hannan and Bell 2000).…”
Section: Case Studies: Seasonal Landscapes Of County Antrimmentioning
confidence: 99%
See 1 more Smart Citation
“…Here a remarkable cluster of more than a hundred earthen houses and relic field systems lie atop an extensive Neolithic occupation. Recent re-evaluation and archaeological survey suggests that rather than being booley huts associated with the practice of seasonal transhumance, as long believed, the houses mark a permanent 17thcentury Highland Scottish village (Horning 2004;Horning and Brannon 2004). Twentieth-century sectarianism has long subjugated awareness of these Roman Catholic Scots who arrived as part of the Ulster Plantation.…”
Section: Out Of the Impasse? Archaeology And Public Discourse In Nortmentioning
confidence: 99%
“…Recent re-evaluation and archaeological survey suggests that rather than being booley huts associated with the practice of seasonal transhumance, as long believed, the houses mark a permanent 17thcentury Highland Scottish village (Horning 2004;Horning and Brannon 2004). Here a remarkable cluster of more than a hundred earthen houses and relic field systems lie atop an extensive Neolithic occupation.…”
Section: Out Of the Impasse? Archaeology And Public Discourse In Nortmentioning
confidence: 99%